Issues at the Rural-Urban Fringe: A Policy Overview of Maintaining Land in Agriculture - Rodney L. Clouser; W. David Mulkey (EDIS)
This fact sheet is one in a series intended to familiarize readers with land use issues at the rural-urban fringe and to identify the techniques that various states, counties, and communities are utilizing to maintain land in agricultural use. Collectively, the fact sheets will provide an overview of common land use conflicts, laws that influence land use at the rural-urban fringe, situational and policy issues related to land use, and the techniques used by governments to deal with these issues. This is EDIS document FE552, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural Urban Fringe". Published July 2005.